2022
DOI: 10.1021/acssuschemeng.1c07621
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Polyimide Powders via Hydrothermal Polymerization and Post-Heat Treatment for Application to Compression-Molding Materials

Abstract: Aromatic polyimides (PIs) are classified as highperformance polymers owing to their excellent thermal, mechanical, and chemical resistance, and they are used widely in aerospace, membranes, microelectronics, and optoelectronics industries. To synthesize aromatic PI powder in an environmentally friendly manner, a hydrothermal polymerization (HTP) method of heating dianhydride and diamine in distilled water in an autoclave has recently been suggested. However, the application of the hydrothermally synthesized PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Polyimides (PIs) are inescapable and irreplaceable raw materials in engineering plastics, aerospace, and military fields owing to their confluence in heat resistance, good electrical conductivity, ,, and strong mechanical properties. , However, the traditional PIs are derived from fossil-based raw materials, which not only bring environmental pollution during the refining process but also speed up fossil fuel depletion. , Sustainable material concepts emphasize reduced fossil-based polymer dependence. Selective transformations of biomass to create PIs provide a promising alternative since biogenic feedstocks use solar energy and CO 2 to produce compounds . In addition, the carcinogenicity of petroleum-derived diamines have posed health challenges for users and sparked widespread controversy. Currently, bio-based PIs have been limited to the addition of bio-based content, which is far from the early goals of revolutionary replacement. This limitation is mainly attributed to the design contradiction between bio-based sources and polymer properties.…”
Section: Introductionmentioning
confidence: 99%
“…Polyimides (PIs) are inescapable and irreplaceable raw materials in engineering plastics, aerospace, and military fields owing to their confluence in heat resistance, good electrical conductivity, ,, and strong mechanical properties. , However, the traditional PIs are derived from fossil-based raw materials, which not only bring environmental pollution during the refining process but also speed up fossil fuel depletion. , Sustainable material concepts emphasize reduced fossil-based polymer dependence. Selective transformations of biomass to create PIs provide a promising alternative since biogenic feedstocks use solar energy and CO 2 to produce compounds . In addition, the carcinogenicity of petroleum-derived diamines have posed health challenges for users and sparked widespread controversy. Currently, bio-based PIs have been limited to the addition of bio-based content, which is far from the early goals of revolutionary replacement. This limitation is mainly attributed to the design contradiction between bio-based sources and polymer properties.…”
Section: Introductionmentioning
confidence: 99%
“…Polyimides have advantageous properties such as good mechanical properties, thermal stability, and chemical resistance [10][11][12][13][14][15][16][17]. Polyimides are also known to have low dielectric constants and thermal conductivity, so they have been widely used in microelectronics, automobiles, and aerospace industries as electronic packaging and electrical insulating materials [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Molding for PIs could be obtained through various approaches, such as compression molding, 6 solid-state extrusion, 7 isostatic pressing, 8 resin transfer molding, 9 etc. Each type of molding possesses its advantages and limitations, however, compared with the other techniques, hot compression molding (HCM) has been widely used owing to its lower cost, good morphological control, and ease of processing.…”
Section: Introductionmentioning
confidence: 99%
“…Zalaznik 19 also demonstrated that the processing temperature below the melting point for polyetheretherketone (PEEK) greatly influenced the crystallinity and hardness, thus determining its tribological behavior. However, the common commercially available non-meltable PIs with glass-transition temperature (T g ) value above 300°C, including trademarks of VESPEL ® , MELDIN ® , and PLAVIS ® respectively from DuPont, Saint Gobain, and Daelim, 20 as well as some scientific investigations, 6,21 were composed of pyromellitic dianhydride (PMDA) and 4.4 0 -diaminodiphenyl ether (ODA). It permits processing only by hot isostatic pressing or powder metallurgy techniques in an oxygenfree environment as well as involves a complicated multistage manufacturing process.…”
Section: Introductionmentioning
confidence: 99%